Selected Forms of Support for the Development of Small and Medium-Sized Enterprises (SMEs) by the Public Sector at the Local and Regional Level - Zbigniew GRZYMAŁA; Grzegorz MAŚLOCH (Communications of International Proceedings, 2020)
Supporting the sector of small and medium-sized enterprises (SMEs) by public sector institutions takes place through a variety of instruments such as: ranging from advisory and educational programs to financial support through various loan funds, subsidies, including grants in EU funds in the case of European Union countries. The purpose of the article is to present partial research as a part of a research project carried out by the Kujawsko-Pomorskie Voivodeship, the Warsaw School of Economics and the Nicolaus Copernicus University in Toruń. These institutions are as a part of the Gospostrateg - Regiogmina project: "Location of support instruments for SMEs at the level of local governments, operating on the basis for a model of multi-level regional governance”. Examples of such support in several analysed countries out of 16 respondents and assumptions of such support for the Kuyavian-Pomeranian Voivodeship are presented. The main purpose was to focus on financial instruments, including the developed of “Local Economic Development Fund (LFRG)”, which may be one of the instrument supporting small and medium-sized enterprises in a given local or regional area. The concept is based on a combination of the initiative of representatives of the regional and local public sector and private entities, mainly entrepreneurs with SMEs.
Keywords: SMEs; Public sector; enterprise support.